Leaf anatomy of emerald grass submitted to quantitative application of herbicides - Marques, Renata Pereira; Martins, Dagoberto [UNESP]; Rodella, Roberto Antonio [UNESP]; Costa, Saulo Ítalo Almeida; Vitorino, Hermeson Dos Santos (Universidade Estadual de Londrina, 2016)
The aim of this work was to evaluate the selectivity of herbicides applied in post-emergence on Zoysia japonica Steud (Poaceae) and determine associations with the leaf anatomy of this grass. The experimental design was randomized blocks with four replications. The treatments were the application of the herbicides bentazon (720 g ha-1), nicosulfuron (50 g ha-1), halosulfuron (112.5 g ha-1), oxadiazon (875 g ha-1) and 2.4-D (698 g ha-1), plus a control treatment without herbicide application. Phytotoxicity was assessed every seven days after application (DAA) of the herbicides until the symptoms disappeared. Foliar anatomical analyses of the leaves in the collected grass were conducted until the 35th DAA. The quantitative characters of the keel and wing region of the blade of Z. japonica were assessed, as well as the biometric characters, which were submitted to an analysis of variance F test, and the averages were compared by Tukey's test at a probability of 5%. The values of the anatomical characters of the foliar blade were tested by cluster analysis. The application of herbicides did not negatively influence the height of the plants but did reduce their dry mass. Toxic symptoms disappeared after 21 DAA, with the only symptoms of injury observed in plants treated with the herbicides oxadiazon and nicosulfuron. In addition, the cluster analysis indicated the formation of a unique discriminatory group. Thus, the results show that the herbicides applied to Z. japonica were selective for the species.
Keywords: Lawns; Plant anatomy; Selectivity; Zoysia japonica